2019
DOI: 10.1186/s12898-019-0227-y
|View full text |Cite
|
Sign up to set email alerts
|

Protura are unique: first evidence of specialized feeding on ectomycorrhizal fungi in soil invertebrates

Abstract: Background Ectomycorrhizal fungi (ECM) play a central role in nutrient cycling in boreal and temperate forests, but their role in the soil food web remains little understood. One of the groups assumed to live as specialised mycorrhizal feeders are Protura, but experimental and field evidence is lacking. We used a combination of three methods to test if Protura are specialized mycorrhizal feeders and compared their trophic niche with other soil invertebrates. Using pulse labelling of young beech an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 54 publications
3
23
0
Order By: Relevance
“…The production rate of the extra-matrical mycelia of ECM fungi in the upper 10 cm of forest soil has been estimated to be about 160 kg dry matter ha −1 y −1 (Ekblad et al, 2013) and due to large biomass of ECM fungi it has been suggested as an important food resource for soil invertebrates (Fitter and Garbaye, 1994;Pollierer et al, 2012). However, recent evidence indicates that consumption of ECM fungi by soil invertebrates is limited (Potapov and Tiunov, 2016;Bluhm et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The production rate of the extra-matrical mycelia of ECM fungi in the upper 10 cm of forest soil has been estimated to be about 160 kg dry matter ha −1 y −1 (Ekblad et al, 2013) and due to large biomass of ECM fungi it has been suggested as an important food resource for soil invertebrates (Fitter and Garbaye, 1994;Pollierer et al, 2012). However, recent evidence indicates that consumption of ECM fungi by soil invertebrates is limited (Potapov and Tiunov, 2016;Bluhm et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…In general, Protura can be found wherever decaying organic matter and sufficient moisture levels are available [1,8], and often are restricted to habitats characterized by luxuriant vegetation growth [7]. It is believed that proturans are fungivorous and some species may feed preferentially on ectomycorrhizal fungi [41]. It is not surprising, therefore, that proturans have rarely been collected in tundra biome, which marks the northern limit of their distribution.…”
Section: Discussionmentioning
confidence: 99%
“…According to Šantrůčková et al 30 , the higher ability of granite to release phosphorous into the soil supports higher microbiologically mediated P-fluxes. This essential nutrient can directly mediate root colonization by mycorrhizal fungi 43 , which provide a major food resource for proturan 23 . Thus the relationship between proturans and differences in soil geochemistry between the catchments can be related to the indirect influence of bedrock on fungal community composition.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lack of appropriate data on proturan feeding ecology and trophic relationships prevents us from informed connections between species distributions and their potential food resources, the preference of at least some species for ectotrophic mycorrhizal fungi was shown by some authors e.g. 23 . This indicates that proturans can be highly sensitive to soil geochemistry and environmental changes that impact mycorrhizae.…”
Section: Discussionmentioning
confidence: 99%